2017
DOI: 10.1111/tbj.12859
|View full text |Cite
|
Sign up to set email alerts
|

Complex sclerosing lesions and radial sclerosing lesions on core needle biopsy: Low risk of carcinoma on excision in cases with clinical and imaging concordance

Abstract: Complex or radial sclerosing lesions (CSL/RSL) are uncommon diagnoses on core needle biopsy with a reported upgrade rate ranging between 0% and 23%. As a result, their management remains controversial. In this study, we sought to determine the rate of malignancy on excision for patients with pure CSL/RSL on core biopsy, and to evaluate future breast cancer risk when CSL/RSL is managed without excision. We retrospectively reviewed 118 cases of CSL/RSL diagnosed on image-guided breast biopsies between 2005 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As noted by several authors, carcinomas found on surgical excision were mainly DCIS, especially of low and intermediate grade, raising the question of over diagnosis of slow‐growing lesions, for which a diagnostic delay due to non‐invasive management would not have a significant impact on prognosis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by several authors, carcinomas found on surgical excision were mainly DCIS, especially of low and intermediate grade, raising the question of over diagnosis of slow‐growing lesions, for which a diagnostic delay due to non‐invasive management would not have a significant impact on prognosis …”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported a significant risk of missed associated carcinoma when RS/CSL is diagnosed on percutaneous biopsy . Others have suggested that percutaneous biopsies are reliable for excluding malignancy, especially when VALCBs are performed . This is mainly due to reports of heterogeneous series.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews show RS account for 5%‐9% of findings on CNB which is a significant proportion of atypical findings 6 . Upgrade rates of RS to atypia or malignancy, however, range widely (0%‐40%) 7,8 . There has also been suggestion that the type of CNB impacts upgrade rates but the general conclusion reached from this research advises observation of patients with RS and no other atypia 4,9‐12 .…”
Section: Introductionmentioning
confidence: 75%
“…Although research has reported that SA may convey an approximate doubling of breast cancer risk as a single feature, the presence of sclerosing adenosis alone in a core biopsy does not require surgical excision ( 29 , 30 ). Close clinical follow-up or routine imaging is recommended ( 1 , 7 , 31 ). Accurately distinguishing SA from invasive carcinoma via a non-invasive, preoperative method is crucial to help avoid unnecessary biopsy and surgery for both patients and clinicians.…”
Section: Discussionmentioning
confidence: 99%